The impact project: Improving the impact of existing malaria products – Acts - Barnes, K; Guérin, P; Hodel, E; Humphreys, G; Pace, C; Banda, C; Denti, P; Allen, E; Lalloo, D; Mwapasa, V; Terlouw, A (BMJ Publishing Group, 2017)
The antimalarial dihydroartemisinin-piperaquine (DHA-PPQ) is one of the recommended drugs to treat uncomplicated Plasmodium falciparum malaria. However, DHA-PPQ has a relatively narrow, poorly defined therapeutic dose range and it is unclear whether PPQ concentration-dependent cardiotoxicity (QTc prolongation) poses a clinical risk for specific subgroups. Uncertainty about the exact safe upper PPQ concentration threshold and recognition of the vulnerability of children has led WHO to consider a complex weight-based dosing regimen. These complex dosing schemes may challenge DHA-PPQ introduction into national control programmes. It also highlights the urgent need to standardise the dose optimisation process.